2020
DOI: 10.1038/s41598-020-59749-y
|View full text |Cite|
|
Sign up to set email alerts
|

Resolving the positions of defects in superconducting quantum bits

Abstract: Solid-state quantum coherent devices are quickly progressing. Superconducting circuits, for instance, have already been used to demonstrate prototype quantum processors comprising a few tens of quantum bits. This development also revealed that a major part of decoherence and energy loss in such devices originates from a bath of parasitic material defects. However, neither the microscopic structure of defects nor the mechanisms by which they emerge during sample fabrication are understood. Here, we present a te… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 28 publications
5
45
0
Order By: Relevance
“…It is becoming increasingly evident that the most coherence-limiting two-level systems (TLS) reside outside the qubit junctions on the surface of metals and dielectrics surrounding them (1)(2)(3)(4)(5) and their slowly fluctuating dynamics poses a serious challenge for quantum computation (1,(5)(6)(7)(8). A wide range of techniques has been developed to study such TLS by developing qubits and resonators into probes of a wide range of material properties (2,5,(9)(10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…It is becoming increasingly evident that the most coherence-limiting two-level systems (TLS) reside outside the qubit junctions on the surface of metals and dielectrics surrounding them (1)(2)(3)(4)(5) and their slowly fluctuating dynamics poses a serious challenge for quantum computation (1,(5)(6)(7)(8). A wide range of techniques has been developed to study such TLS by developing qubits and resonators into probes of a wide range of material properties (2,5,(9)(10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…and contamination at electrode interfaces are major limiting factors for qubit coherence [4][5][6][7].…”
Section: In-situ Bandaged Josephson Junctions For Superconducting Quantum Processorsmentioning
confidence: 99%
“…Extensive studies in recent decades have identified major noise sources in superconducting qubits, including * leonid.abdurakhimov.nz@hco.ntt.co.jp parasitic two-level-system (TLS) defects [13][14][15][16][17][18][19][20][21][22][23][24][25][26], quasiparticle noise [27][28][29][30][31][32][33][34][35][36][37], and, for flux-tunable qubits, a 1/f magnetic flux noise [38,39]. In this paper, we focus on TLS defects: defects of different microscopic nature that can be modeled as two-level quantum systems, such as tunneling atoms, dangling electronic bonds, impurity atoms, and trapped charge states [21].…”
Section: Introductionmentioning
confidence: 99%
“…Normally, it is assumed that the qubit-defect interaction is caused by an electric-field coupling between an electric dipole associated with a charge TLS defect and a microwave electric field generated across a Josephson junction [14]. The standard techniques to study high-frequency TLS defects in superconducting qubits are based on matching the frequencies of qubit and defect transitions either by adjusting the qubit frequency with an applied magnetic flux [13,14,16,45,46] or changing the defect frequency with an external electrical field or an applied mechanical strain [17,[22][23][24]. Parameters of a TLS defect are then extracted from the splitting of an avoided crossing observed in the qubit spectrum [13,14], the qubit response to a Rabi drive [45], or measurements of energyrelaxation times [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation